Boosting reversible oxygen electrocatalysis with enhanced interfacial pyridinic-N–Co bonding in cobalt oxide/mesoporous N-doped graphene hybrids. Issue 47 (28th November 2018) - Feng, Ting; Zhao, Xue-Ru; Dong, Cun-Ku; Liu, Hui; Du, Xi-Wen; Yang, Jing
Abstract : A hybrid catalyst CoO/mesoporous N-doped graphene with enhanced pyridinic-N–Co bonding is designed and it exhibits superior bi-functional ORR/OER performance. Abstract : A hybrid electrocatalyst CoO/r-NLG with a high density of pyridinic-N–Co bonds was synthesized via pyrolysis treatments of a mixture of cobalt iron precursors and laser-induced mesoporous N-doped graphene, which achieved superb reversible ORR/OER activities, offering a low efficiency loss (Δ E ) of 0.635 V in a 1.0 M KOH electrolyte.